Studies on the mechanism of inhibition of chemotactic tripeptide stimulated human neutrophil polymorphonuclear leucocyte superoxide production by chloroquine and hydroxychloroquine. - Hurst, N P (1987)
The effect of chloroquine and hydroxychloroquine on neutrophil superoxide release stimulated by the chemotactic tripeptide N-formyl-methionyl-leucyl-phenylalanine (FMLP) was examined. Both drugs caused time and dose dependent inhibition of superoxide release but had no effect on equilibrium binding of [3H]FMLP to its receptor. Preliminary experiments suggest that these drugs may exert their inhibitory effect on superoxide release by inhibiting the FMLP stimulated hydrolysis of phosphoinositides.